2016
DOI: 10.1159/000443076
|View full text |Cite
|
Sign up to set email alerts
|

Rac1/β-Catenin Signalling Pathway Contributes to Trophoblast Cell Invasion by Targeting Snail and MMP9

Abstract: Background/Aims: Preeclampsia is an idiopathic and serious complication during gestation in which placental trophoblast cells differentiate into several functional subtypes, including highly invasive extravillous trophoblasts (EVTs). Although the cause and pathogenesis of preeclampsia have remained unclear, numerous studies have suggested that the inadequacy of EVT invasion leads to imperfect uterine spiral artery remodelling, which plays a crucial role in the development of preeclampsia. Rac1, or Ras-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
1
24
0
1
Order By: Relevance
“…In this study, we provide evidence that, hypoxia or AICAR treatment significantly increased ROS production in HTR8/SVneo cells, while inhibition of FA β-oxidation totally diminished AICAR promoted ROS production. MMPs are known important for trophoblast invasion [52], although an inhibitory effect of AMPK on MMPs has recently been reported in endothelial progenitor cells and in human umbilical vein endothelial cells [53,54], the present study is the first to demonstrate that AMPK inhibits MMP2 in trophoblast, probably by promoting ROS generation from FA β-oxidation.…”
Section: Discussionmentioning
confidence: 45%
“…In this study, we provide evidence that, hypoxia or AICAR treatment significantly increased ROS production in HTR8/SVneo cells, while inhibition of FA β-oxidation totally diminished AICAR promoted ROS production. MMPs are known important for trophoblast invasion [52], although an inhibitory effect of AMPK on MMPs has recently been reported in endothelial progenitor cells and in human umbilical vein endothelial cells [53,54], the present study is the first to demonstrate that AMPK inhibits MMP2 in trophoblast, probably by promoting ROS generation from FA β-oxidation.…”
Section: Discussionmentioning
confidence: 45%
“…Among members of MMP family, MMP-2 and MMP-9 were suggested to play an important role in the regulation of trophoblast invasion [31, 32]. Our results showed that reduction of NTE markedly inhibited the production of MMP-9 of HTR-8/SVneo Cells, which was in correspondence with the change of trophoblast cells migration and invasion.…”
Section: Discussionsupporting
confidence: 51%
“…Rac1, Cdc42, and ROCK are involved in prostaglandin E 2 -stimulated trophoblast cell migration, and RhoGDI2 inhibits trophoblast cell migration by suppression of Rac1 activity [21][22][23]. Decreased Rac1 activities have been observed in pre-eclamptic placentas and genetic ablation of mouse Rock2 leads to placental dysfunction and IUGR [24][25][26].…”
Section: Introductionmentioning
confidence: 99%